Human serum albumin and oxidative stress in preeclamptic women and the mechanism of albumin for stress reduction. Issue 8 (August 2017) - Kinoshita, Hiroyuki; Watanabe, Kazushi; Azma, Toshiharu; Feng, Guo-Gang; Akahori, Takahiko; Hayashi, Hisaki; Sato, Motohiko; Fujiwara, Yoshihiro; Wakatsuki, Akihiko
Abstract: Aims: The present study to address one of the mechanisms in preeclampsia, examined whether levels of oxidative stress, human serum albumin, and endothelial function correlate in pregnant women and whether human serum albumin reduces levels of superoxide produced by NADPH oxidase activation in the human vascular smooth muscle cells. Materials and methods: Pregnant women with (Preeclampsia group, n = 33) and without preeclampsia (Normal group, n = 37) were recruited to determine levels of reactive oxygen species (serum diacron-reactive oxygen metabolite [d-ROM]), and the flow-mediated dilation (FMD). Human coronary arterial smooth muscle cells or omental arteries were subjected to evaluate isometric force recordings, levels of superoxide, western immunoblotting, and immunohistochemistry. The superoxide scavenging assay was also performed in a cell-free system. Key findings: Women in the preeclampsia group demonstrated lower FMD and higher serum d-ROM values than those in the normal group. There were the inverse correlations between serum levels of d-ROM and the degree of FMD and between serum levels of albumin and those of d-ROM. D-glucose reduced the levcromakalim-induced dilation of human omental arteries, and it increased levels of superoxide and the recruitment of the NADPH oxidase subunit p47phox in human coronary arterial smooth muscle cells. Human serum albumin (0.05 to 0.5 g/dL) prevented these alterations whereas it exerted no superoxide scavenging effect. Significance: Serum albumin relates to oxidative stress inversely, but to the endothelial function positively, in pregnant women. Human serum albumin appears to reduce oxidative stress via NADPH oxidase inhibition in the human vascular smooth muscle, indicating that the serum level may be a critical determinant of vascular oxidative stress in some human diseases.